Land Dispute Settlement Through Mediation In The Regional Land Office In Boyolali Regency - Sarsono Sarsono; Joseph Diko Reinol Panjaitan; Munsharif Abdul Chalim (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2018)
This study aims to describe the settlement of land disputes through mediation conducted in Regional Land Office of Boyolali Regency, and the obstacles encountered in settling land disputes through mediation. So, it can provide additional knowledge for anyone who reads it. The problem formulation in this research is how the role of the land office in order to settle the land dispute mediation in the Land Office of Boyolali Regency and what are the constraints of the mediation in land disputes in the Land Office of Boyolali Regency. This research is a legal juridical empirical research or legal sociology research. It it kind of research that analyzes a problem by combining secondary data (legislation) with primary data obtained in the field. The result of this research is that the role of Land Affair Office of Boyolali Regency in the effort of settling land dispute through mediation is as mediator who is responsible for assisting the parties in dispute to produce agreement received by the all parties. The parties assist to end up the dispute, then pour the result of mediation into the Minutes of Mediation. In the event of mediation, when the agreement is reached, the parties are willing to implement the mediation decision. However, if in mediation is not reached agreement, the District Office of Boyolali Regency will invites the parties to process through litigation (court). In the implementation of mediation at the Land Office of Boyolali Regency, there are obstacles, namely: (1) The absence of the parties in dispute, (2) there is no good intentions from each party in dispute, (3) Differences in ability and education among the parties, (4) The role of Land Office of Boyolali Regency is only as mediator, it cannot be as a decision maker/court.Keywords: Settlement Of Land Dispute, Mediation, Land Office.